ANALISYS OF FACTORS THAT INFLUENCENON-MUSLIM CUSTOMERS' DECISION TO USE BANK SINARMAS SYARIAH MEDAN BRANCH - Elsa Noviliani Syarif Emil; Endang Sulistya Rini; Isfenti Sadalia (CV. Radja Publika, 2026)
In the aspect of Sharia banking knowledge, it was found that customers only know that saving in Sharia banking, especially at Bank Sinarmas Syariah Branch Offices, will get benefits from the profit sharing system (not from interest/riba) while for the operational system of Sharia banking itself, the majority of customers do not know. This is also in line with the knowledge of customers who mostly only know Sharia products such as: murabahah and mudharabah while other products customers do not know. The objectives of this study are to: 1) Analyze the influence of Location on Customer Decisions to Save at Bank Sinarmas Syariah Medan Branch, 2) Analyze the influence of Service Quality on Customer Decisions to Save at Bank Sinarmas Syariah Medan Branch, 3) Analyze the influence of Administrative Profits on Customer Decisions to Save at Bank Sinarmas Syariah Medan Branch,4) Analyze the influence of Knowledge on Customer Decisions to Save at Bank Sinarmas Syariah Medan Branch, 5) Analyze the influence of Products on Customer Decisions to Save at Bank Sinarmas Syariah Medan Branch, 6) To Analyze the influence of Promotions on Customer Decisions to Save at Bank Sinarmas Syariah Medan Branch and 7) Analyze the influence of Location, Service Quality, Benefits, Knowledge, Products, and Promotions on Customer Decisions to Save at Bank Sinarmas Syariah Medan Branch. The research was conducted at the Sinarmas Syariah Medan Branch Office, Jalan Iskandar Muda No. 33, Medan.